Human Oral Keratinocytes Challenged by Streptococcus sanguinis and Porphyromonas gingivalis Differentially Affect the Chemotactic Activity of THP-1 Monocytes - Li, Huajing; Seneviratne, Chaminda Jayampath; Jin, Lijian (International Journal of Microbiology, 2022)
Periodontal diseases are initiated by the shift from microbe-host symbiosis to dysbiosis, and the disrupted host response predominantly contributes to tissue destruction. This study investigated whether and to what extent human oral keratinocytes (HOKs) challenged by a periodontal commensal or pathogen could differentially affect the chemotactic activity of THP-1 monocytes. A selected periodontal commensal (Streptococcus sanguinis ATCC 10556) and a pathogen (Porphyromonas gingivalis ATCC 33277) were cultured and inoculated, respectively, into the lower chamber of Transwell® Permeable Supports with HOKs and incubated for 2 h or 18 h at 37°C under appropriate cell growth conditions. HOKs alone served as the control for the transwell migration assay. Well-stained THP-1 monocytes were seeded in the top chamber of the device, incubated for 2 h and then collected from the lower well for quantitation of the migrated fluorescence-labeled cells by the FACSCalibur™ flow cytometer. The statistical significance was determined using one-way ANOVA. The HOKs challenged by S. sanguinis attracted a significantly higher number of THP-1 cell migration as compared with the control after 2 h or 18 h interaction (p<0.01). By contrast, P. gingivalis-treated HOKs exhibited a markedly reduced chemotactic effect on THP-1 cells (p<0.01, 2 h; p<0.05, 18 h). There was no significant difference in THP-1 cell migration among the groups with either S. sanguinis or P. gingivalis alone. The current findings on P. gingivalis-HOKs interactions with resultant paralysis of THP-1 cell chemotaxis provide further evidence that the keystone periodontopathogen P. gingivalis can evade innate defense and contribute to periodontal pathogenesis.